Employment generation in African agriculture - Eicher, Carl K.; Zalla, Thomas; Kocher, James; Winch, Fred; Institute of International Agriculture, College of Agriculture and Natural Resources (East Lansing: Michigan State University, 1970)
This book explains the explosive rates of urbanization as common problems to almost all developing countries. It further examine the rates of employment drive in Agriculture in Africa.
Bibliography: p. 58-66.
asm; 27/02/19
Loans
Keywords: Unemployed; Agricultural laborers; Agriculture and state